Evaluating Capacity Of Palm Oil Mill Using Simulation Towards Effective Supply Chain - A Case Study - Razman, Mat Tahar (2011)
The purpose of this study is to evaluate the current capacity of the palm oil processing mill using simulation. We choose to simulate the current facility in order to analyze the processing operations of the mill and determine the capacity planning measures to be undertaken in the future in meeting the increase volume . The operations including the downtime due to machine breakdown or any mechanical problems will be evaluated. Simulation will be used in identify the key failure of components or machines during operations. It is expected that this simulation will help mill manager to identify how the system would handle future forecast of production with the current capacity and the increase volume in supply of fresh fruit bunches to the mill